2020
DOI: 10.3389/fmech.2020.601510
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of Crater-Enabled Soft Dry Adhesives: A Review

Abstract: Dry adhesion is governed by physical rather than chemical interactions. Those may include van der Waals and electrostatic forces, friction, and suction. Soft dry adhesives, which can be repeatedly attached to and detached from surfaces, can be useful for many exciting applications including reversible tapes, robotic footpads and grippers, and bio-integrated electronics. So far, the most studied Soft dry adhesives are gecko-inspired micro-pillar arrays, but they suffer from limited reusability and weak adhesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 123 publications
(194 reference statements)
0
3
0
Order By: Relevance
“…3a). Micro-crater (sucker cup)-based dry adhesives retain their adhesive strength even in humid conditions and underwater 134 , but they cannot match microfibres in terms of adhesion strength.…”
Section: Soft Grippersmentioning
confidence: 99%
“…3a). Micro-crater (sucker cup)-based dry adhesives retain their adhesive strength even in humid conditions and underwater 134 , but they cannot match microfibres in terms of adhesion strength.…”
Section: Soft Grippersmentioning
confidence: 99%
“…To sum up, the reasons why the gully-like structures can help aquatic organisms improve their attachment capacity are mainly reflected as follows [ 60 , 61 ]: (1) The gully-like structures help to achieve the peripheral extension of the biological soft suction cups and increase the contact with the surfaces of objects. (2) The softer structures, such as wrinkles, pits, and grooves, can help the suction cups to achieve space compensation when they contact irregular contacting surfaces, and the increasing friction between the contacting surfaces makes the sucker have higher attachment performance.…”
Section: Non-smooth Structural Morphologies and Attachment Mechanisms...mentioning
confidence: 99%
“…Among the various species, gecko lizards, beetles, octopuses, and remoras have attracted substantial attention owing to their excellent adhesion properties, such as high adhesion to curved or rough target surfaces, functionality in wet environments, reusability, and biocompatibility (Figure 1A) (Autumn et al, 2000;Dirks and Federle, 2011;Baik et al, 2017;Wang et al, 2017). Extensive studies over the past two decades have revealed that their superior adhesion properties originate from their unique terminal structures (Wang L. et al, 2020). For example, gecko lizards and beetles can walk freely on walls or ceilings with strong adhesion based on numerous pillar structures with spatulated or mushroom-shaped tips on their toes (Autumn et al, 2000;Arzt et al, 2003;Jeong et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%